Research in the social scientific study of religion - Piedmont, Ralph L., 1958- (Research in the Social Scientific Study of Religion, 2007)
Research in the Social Scientific Study of Religion (RSSSR) publishes reports of innovative studies that pertain empirically or theoretically to the scientific study of religion, including spirituality, regardless of their academic discipline or professional orientation. RSSSR is published annually with the kind support of Loyola College, Maryland, USA. This volume of RSSSR contains several articles on spiritual development among adolescents, spiritual transcendence, Jung and pastoral counseling and spirituality and religiosity. In addition to this, a special section of nine articles is devoted to several aspects of positive psychology and its usage in practice.